Influence of Social Media Marketing And Celebrity Endorsement On Purchasing Decisions Skintific Products In Garut City - Arrasyid, Fuji Fitriana; Hermina, Tinneke; Wufron, Wufron (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: The purpose of this study is to investigate how social media and the selebriti environment affect consumers' decisions to purchase skintific products in Garut. Methodology: Non-probability sampling, which is used for sample selection, is used to analyze quantitative data. The sample in this study consists of 100 respondents. The data was collected using a questionnaire and analyzed using a linear regression. Results: The results of the berganda regression analysis show that Y = 0.075 + 0.176 (X1) + 0.719 (X2) + 0.27 (ε) indicates a positive relationship between the two variables and the pembelian's response. A coefficient of determination (R2) of 0.730 indicates that 73.0% of the study's findings are influenced by the factors mentioned above, while 27% are caused by unidentified variables. Findings: The findings indicate that celebrity endorsements and social media marketing have a big impact on consumers' decisions to buy. Celebrity endorsement boosts consumer trust, while social media marketing offers engagement and information. Originality: This study expands our understanding of how marketing strategies that integrate social media and celebrity endorsement might expand consumer choice in a competitive industry like skincare and gives a summary of the role of social media influencers. Novelty: This study sheds insight on the relationship between social media marketing and celebrity endorsement in relation to skincare product purchases, an area that has not received much attention in earlier studies. In Conclusion, Skintific should prioritize authenticity, engagement, and credibility in its influencer partnerships and social media marketing approach in order to optimize sales. Type of paper: Empirical research type.